2017
DOI: 10.1021/acs.jmedchem.6b01733
|View full text |Cite
|
Sign up to set email alerts
|

Target Elucidation by Cocrystal Structures of NADH-Ubiquinone Oxidoreductase of Plasmodium falciparum (PfNDH2) with Small Molecule To Eliminate Drug-Resistant Malaria

Abstract: Drug-resistant malarial strains have been continuously emerging recently, which posts a great challenge for the global health. Therefore, new antimalarial drugs with novel targeting mechanisms are urgently needed for fighting drug-resistant malaria. NADH-ubiquinone oxidoreductase of Plasmodium falciparum (PfNDH2) represents a viable target for antimalarial drug development. However, the absence of structural information on PfNDH2 limited rational drug design and further development. Herein, we report high reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 46 publications
(70 reference statements)
3
55
0
Order By: Relevance
“…Notably, RYL-552 binds three different binding regions within 5jwc far from the NADH/FAD/UQ cofactor-binding area. While two of those regions appear to be poorly resolved, the third ones appears to be a specific binding cavity [45]. By superimposing 5jwc with the analyzed AIF, NDI, and NDH-2, it appears that NDH-2 and NDI might form several interactions with RYL-552 involving 8 and 11 residues, respectively, that appear to be further well conserved in the sampled NDH-2 and NDI-like proteins (although in the latter, the overlapping binding region appears more buried from the local secondary structure), at variance with the AIF showing a lower number of interacting residues (just four, see Supplementary Table S6 and Supplementary Figure S4).…”
Section: Small Molecules and Other Cofactor-binding Regionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Notably, RYL-552 binds three different binding regions within 5jwc far from the NADH/FAD/UQ cofactor-binding area. While two of those regions appear to be poorly resolved, the third ones appears to be a specific binding cavity [45]. By superimposing 5jwc with the analyzed AIF, NDI, and NDH-2, it appears that NDH-2 and NDI might form several interactions with RYL-552 involving 8 and 11 residues, respectively, that appear to be further well conserved in the sampled NDH-2 and NDI-like proteins (although in the latter, the overlapping binding region appears more buried from the local secondary structure), at variance with the AIF showing a lower number of interacting residues (just four, see Supplementary Table S6 and Supplementary Figure S4).…”
Section: Small Molecules and Other Cofactor-binding Regionsmentioning
confidence: 98%
“…The main differences between the five structures are at the level of their C-terminus portion. Notably, 5jwc.pdb [45] shows a 70-aa long extra loop (residues 363-433, 5jwc.pdb numbering (Figure 4)).…”
Section: Sampling Of Homologous-crystallized Structures By Folding Rementioning
confidence: 99%
See 1 more Smart Citation
“…To date, crystal structures of NDH-2 have been determined for only the following four species: Saccharomyces cerevisiae (Feng et al, 2012;Iwata et al, 2012), Caldalkalibacillus thermarum (Heikal et al, 2014), Staphylococcus aureus (Sena et al, 2015) and P. falciparum (Yang et al, 2017). NDH-2 consists of three domains.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, our group solved the X-ray structures of Ndi1 (NDH2 from yeast) in apo, NADH-, Q-, and NADH-Q-bound states and demonstrated that electron transfer in NDH2 requires two Q molecules and CTD of NDH2 mediates the homodimerization and membrane attachment (Feng et al, 2012). Later on, our group reported the X-ray structures of PfNDH2 (NDH2 from P. falciparum) in its apo, NADH-, and RYL-552 (a new inhibitor)bound states, unveiling the inhibiting mechanism of PfNDH2 and providing accurate information for designing new antimalarial drugs (Yang et al, 2017).…”
Section: Pre-structural Age Their Existence and Their Functionmentioning
confidence: 99%